2020
DOI: 10.1038/s41598-020-69207-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function parameters as a tool for tailored drug treatment of an individual with psychosis: a proof of concept study

Abstract: pharmacological treatment of mental disorders is currently decided based on "trial and error" strategy. Mitochondrial multifaceted dysfunction is assumed to be a major factor in the pathophysiology and treatment of schizophrenia (SZ) and bipolar disorder (BD). This study aimed to explore the feasibility of using a profile of mitochondrial function parameters as a tool to predict the optimal drug for an individual patient (personalized medicine). Healthy controls (n = 40), SZ (n = 48) and BD (n = 27) patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…As indicated by Bar-Yosef et al, patient response to treatment was associated with mitochondrial parameters, approximately half of the mitochondrial parameters (respiratory parameters) were improved in patients with schizophrenia who were responsive, but these parameters returned to normal only in those who received long-term treatment. 62 Our results also indicated that parameters related to mitochondrial impairment in lymphocytes might be predictors of patient response. Nevertheless, no significant improvement was found in the mitochondrial damage in CD3, CD4, and CD8 lymphocytes after treatment, which might be due to the short follow-up duration (about 24 days) in this study.…”
Section: Discussionsupporting
confidence: 54%
“…As indicated by Bar-Yosef et al, patient response to treatment was associated with mitochondrial parameters, approximately half of the mitochondrial parameters (respiratory parameters) were improved in patients with schizophrenia who were responsive, but these parameters returned to normal only in those who received long-term treatment. 62 Our results also indicated that parameters related to mitochondrial impairment in lymphocytes might be predictors of patient response. Nevertheless, no significant improvement was found in the mitochondrial damage in CD3, CD4, and CD8 lymphocytes after treatment, which might be due to the short follow-up duration (about 24 days) in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Future antipsychotic medication studies should include genetic and non-genetic biomarkers for the potential to develop antipsychotic-induced dopamine supersensitivity psychosis, aiDSP and treatment resistance, and various forms of oxidative stress and genetic metabolic responses, which may affect dropout rates, side effect profiles, and outcomes more generally. It is now possible to track longterm antipsychotic side effects such as cognitive decline and metabolic syndrome more precisely (Bar-Yosef et al, 2020;Cem Atbaşoglu, Schultz, & Andreasen, 2001;Joshi et al, 2021;Scaini et al, 2018). We, therefore, recommend that researchers follow biomarker adaptive antipsychotic medication clinical trial designs, in order to control for a myriad of molecular confounders and long-term side effects (Perkovic et al, 2017).…”
mentioning
confidence: 99%
“…Effects of first- and second-generation antipsychotics were evaluated by an in vitro analysis of mitochondrial proteins in the lymphocytes of psychotic patients [ 270 ]. The hierarchical clustering dendrogram showed a separate cluster for first- and second-generation compounds, suggesting the possibility of exploiting mitochondrial function parameters as a tool for tailored drug treatment in patients with schizophrenia or bipolar disorder [ 270 ]. Olanzapine and risperidone were effective in decreasing mitochondrial maximal respiration [ 270 ].…”
Section: Antipsychotic Treatment Effects On Mitochondrial Function An...mentioning
confidence: 99%
“…The hierarchical clustering dendrogram showed a separate cluster for first- and second-generation compounds, suggesting the possibility of exploiting mitochondrial function parameters as a tool for tailored drug treatment in patients with schizophrenia or bipolar disorder [ 270 ]. Olanzapine and risperidone were effective in decreasing mitochondrial maximal respiration [ 270 ]. Olanzapine decreased levels of caspase 3 and MFN1, whereas risperidone significantly decreased OPA1 protein levels [ 270 ].…”
Section: Antipsychotic Treatment Effects On Mitochondrial Function An...mentioning
confidence: 99%
See 1 more Smart Citation